Answer:
:
Solve:
-X - Y - Z =-8
- 4X +4Y +5Z=7
2X + 2Z =4 is the same as x + z = 2. Thus, z = 2 - x.
Subst. 2 - x for z in the 1st and second equations.
-X - Y - Z =-8 becomes -x - y - (2 -x) = -8
- 4X +4Y +5Z=7 becomes -4x + 4y + 5(2-x) = 7
Now we have 2 equations in only 2 unknowns. Let's simplify them!
-x - y - 2 + x = -8 which becomes -y = -6, or y = 6
-4x + 4y + 10 - 5x = 7 which becomes -9x + 4y = 7 - 10 = -3
Now substitute 6 for y in this last equation: -9x + 4(6) = -3, or
-9x + 24 = -3, or
-9x = - 27 => x = 3
Then x = 3, y = 6 and z = 2 - x, or z = 2-3, or z = -1.
The solution is (3, 6, -1). Check it!!